Pentingnya Konsumsi Tempe pada Penderita Diabetes Melitus di Kelompok Ibu-Ibu Senam di Kelurahan Talang Banjar - Iin Indrawati; Maimaznah Maimaznah (Jurnal Abdimas Kesehatan (JAK), 2020)
People with DM have a risk of experiencing coronary heart disease 3.2 times greater than non-sufferers, the risk of having a stroke 2.9 times greater. Effective and efficient DM management requires effective prevention and mitigation programs. One way to prevent this is to know the characteristics of individuals who are at risk of developing DM. The influence of education on dietary regulation is important for DM sufferers.This community service activity is intended to provide a solution for mothers who suffer from DM to want to consume tempe regularly with a predetermined amount. The method of implementation of the activity used was a health check in the form of checking blood sugar for women who participated in gymnastics as well as screening for DM sufferers. Patients who were netted to have DM were collected and given health education about the importance of eating tempe as an effort to control blood sugar without changing the daily habits that are commonly practiced by DM sufferers in terms of food and drug consumption.Community service activities carried out in the form of health education activities in the form of an invitation to the public to want to consume tempeh regularly with a certain amount every day.The results of community service activities have led to the emergence of new habits in terms of daily food consumption by adding tempe menus to food.